1966
DOI: 10.1111/j.1471-4159.1966.tb11955.x
|View full text |Cite
|
Sign up to set email alerts
|

Free Nucleotides in the Rat Brain During Post‐natal Development

Abstract: THE study of the evolution of free nucleotides in the central nervous system (CNS) during post-natal development has not been exhaustive so far. MANDEL, BIETH and WEILL (1957) investigated the adenylic nucleotides by the classical technique of LEPAGE (1949), COHEN and LIN (1962) studied the ATP by column chromatography and enzymic determination, and DEW, MUKUNDAN, SRIVASTAVA and S u m , (1963) analysed the total acid-soluble nucleotides by U.V. absorption. To explore more precisely the evolution of free nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1

Year Published

1976
1976
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(33 citation statements)
references
References 5 publications
3
29
1
Order By: Relevance
“…This peak was chosen for two reasons. First, other studies have indicated that ATP and NTP do not change greatly with age (Samson, Balfour & Dahl, 1960;Mandel & Edel-Harth, 1966;Miller & Shamban, 1977). Secondly, ATP concentration is maintained constant during the course ofan experiment by PCr acting as a buffer (see e.g.…”
Section: Resultsmentioning
confidence: 99%
“…This peak was chosen for two reasons. First, other studies have indicated that ATP and NTP do not change greatly with age (Samson, Balfour & Dahl, 1960;Mandel & Edel-Harth, 1966;Miller & Shamban, 1977). Secondly, ATP concentration is maintained constant during the course ofan experiment by PCr acting as a buffer (see e.g.…”
Section: Resultsmentioning
confidence: 99%
“…These levels are lower than those described in brain samples obtained from rats killed differently (i .e ., by freezing the brain before decapitation and, thereafter, not subjecting the tissues to incubation) (Mandel and Edel-Harth, 1966 ; Abe et al ., 1987) . Dose-dependent increases in tissue CTP levels were observed after striatal slices were incubated with cytidine for l h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of PC biosynthesis apparently depends upon the activity of CTP :phosphocholine cytidylyltransferase, which catalyzes the formation of CDP-choline from phosphocholine and CTP (Pelech and Vance, 1984) . Brain CTP levels are low (Mandel and Edel-Harth, 1966 ;Abe et al ., 1987) and below this enzyme's apparent K , for the nucleotide (Pelech and Vance, 1984 ;Mages et al, 1988) . Hence, we suspected that exogenous cytidine might, by increasing intracellular CTP levels, affect brain phospholipid synthesis .…”
mentioning
confidence: 99%
“…These results indicate that cGMP and cAMP levels in retina are influenced by the light adaptational state, that ischemia markedly modifies these processes, and that the effects of both light exposure and ischemia are regionally selective. Previous studies have detected the existence of adenosine 3': 5'-cyclic monophosphate (cAMP) and guanosine 3':5'-cyclic monophosphate (cGMP) in mammalian retina and have demonstrated that this tissue is uniquely rich in cGMP (1,2). Dark adaptation increases cGMP in outer segments of mammalian photoreceptor cells in vitro (3)(4)(5)(6)(7), and Fletcher and Chader (8) emia was studied.…”
mentioning
confidence: 99%